Incorporation of bacteriophages in polycaprolactone/collagen fibers for antibacterial hemostatic dual‐function. Issue 7 (22nd January 2018) - Cheng, Weilu; Zhang, Zhongyang; Xu, Ruodan; Cai, Panpan; Kristensen, Peter; Chen, Menglin; Huang, Yudong
Abstract: Effective and affordable, antibacterial and hemostatic materials are of great interests in clinical wound care practices. Herein, Enterobacteria phage T4 were incorporated in polycaprolactone/collagen I (PCL‐ColI) nanofibers via electrospinning in order to eradicate Escherichia coli infection and meanwhile establish hemostasis. Tensile strength of the membrane was significantly enhanced with increased PCL ratio. Those with a collagen component above 70% were demonstrated to be more hemostatic with shorter hemostatic time and smaller amount of bleeding. On the other hand, the T4 phage incorporated PCL‐ColI membrane (PCL:ColI = 30%/70%, w/w) exhibited the optimal antibacterial efficiency (above 90%). The in vivo evaluation indicated that the PCL‐ColI B (30%:70%, w/w) membrane fully degraded in 8 weeks and no obvious pathological reaction to muscle and subcutaneous layer tissues in the back of rabbit was found. The novel fibrous hemostatic materials coupled with phage therapy hold great promise in designing novel antibacterial, hemostatic wound dressings that addresses concerns of antibiotic resistance. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2588–2595, 2018.